Profiling of Antarctic sea ice thickness and relevant sea ice structure near Syowa Station by impulse radar (abstract) - Ohmae, Hirokazu; Nishio, Fumihiko; Ishikawa, Masao; Takahashi, Shuhei; Katsushima, Takayoshi (1984)
P(論文) departmental bulletin paper